Morphological Characterization of Tea Hybrid Progeny - Widhianata, Hani; Noviansyah, Novan; Sudibya, Eka; Suwasono, Prayitno Ribut (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2025)
Hybridization is the main method for obtaining genetic diversity and breeding new varieties of tea. The purpose of this research is to determine the morphological potential of each progeny from crossing between male and female parents which can then be used as a source of information in developing high quality superior tea clones through tea breeding activities. Male and female parents with the desired traits were crossed to form genetic diversity. 34 progenies resulted from crosses formed from crossing 4 male parents and 3 female parents. All parents and progeny were characterized morphologically and yield components. Data on morphological characters and yield components were analyzed descriptively. Correlation analysis and Principles Component Analysis Biplot (PCA Biplot) were also performed using R software. Male tea parents and female tea parents are in different groups based on morphological characteristics. Progeny-17, Progeny-18, Progeny-4, Progeny-5, and Progeny-27 had a higher total number of shoot and potential yield per bush compared to the other progenies.